Pengaruh Pofitability, Liquidity, Sales Growth, Dan Asset Structure Terhadap Capital Structure - Albertus Giovanni, Rosmita Rasyid (Jurnal Paradigma Akuntansi, 2021)
The purpose of this research is to show empirically the influence of profitability, liquidity, sales growth, and asset structure on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the 2016-2018 period. The technique of sample selection is using purposive sampling method and obtained a sample of 69 manufacturing companies. The results of the study stated that liquidity and asset structure negatively affect capital structure. While profitability and sales growth has no effect on capital structure.